Stratigraphy and Palaeopedology of the Palaeolithic Cave Site of Combe‐Saunière, Southwest France. Issue 5 (22nd July 2013) - Ajas, Aurélie; Bertran, Pascal; Lemée, Laurent; Queffelec, Alain
<x xml:space="preserve">Abstract</x> The sequence of Combe‐Saunière (southwest France) has been studied with a large suite of methods, including micromorphology, geochemistry, magnetic susceptibility, and organic matter (OM) analysis in order to document the post‐depositional processes that occurred during the last climatic cycle at the cave entrance. This study shows that intense weathering together with the accumulation of OM and phosphates by cave animals and others vectors (including humans) occurred during the phases of low clastic sedimentation. During the latter part of Marine Isotope Stage (MIS) 3, the Aurignacian and Gravettian humus‐bearing levels, which may be classified as cryoturbated leptosols, show incomplete decalcification and are dominated by poorly evolved forms of phosphates (bone fragments, coprolites). Phosphatized cambic B‐horizons formed at the beginning of MIS 3 and the Early Glacial and may reflect longer periods of pedological modification. The molecules identified by the analysis of the OM extracted from the Châtelperronian level derive mostly from the degradation of vegetal matter, most notably from conifers and mosses, in addition to bacteria and fungi. The Last Interglacial s.l. (MIS 5) is typified by the development of a phosphatized illuviated B‐horizon. Intense weathering together with phosphate leaching and precipitation took place in this soil, forming thick apatite–CaOH crusts. Although the poor chronological resolution prevents us from drawing clear conclusions as to the respective roles of the factors involved, phosphate accumulation and weathering seem to be controlled primarily by the duration of the soil‐forming periods. This study strongly suggests that a climatic signal has been recorded in the deposits.